PENGARUH KEPEMILIKAN TERKONSENTRASI DAN ASING TERHADAP REPUTASI PERUSAHAAN - Robert Jao (Jurnal Ilmu Akuntansi, 2021)
The purpose of this study is to analyze the effect of the structure of concentrated ownership and foreign ownership on the corporate's reputation. The population in this study are companies on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The sampling technique used was purposive sampling. The method used in this research is quantitative research methods. Data sources used are secondary data sources obtained from the Indonesia Stock Exchange (IDX) and the Corporate Image Award from 2017 to 2019, the type of documentary data used, namely the company's annual report and survey results from the Corporate Image Index from 2017 to 2019. The results showed that concentrated ownership and foreign ownership had a positive and significant effect on the company's reputation. The higher the concentrated share ownership and shares owned by foreign investors, the better the corporate's reputation.